Sustainable Development as a Model and Artifact of Modern Civilization - Gabitov, Tursun; Alikbayeva, Marzhan; Omirbekova, Aliya; Aljanova, Nurlykhan; Saparova, Dinara (European Journal of Sustainable Development, 2018)
The modern world civilization endures the period of the radical transformation of the sociocultural basements. At simultaneous existence on Earth of all three waves of the civilization (O. Toffler), the dominating value is gained by the fourth industrial revolution. If X?X and the first part of the XX century the content of all-planetary civilization processes radically changes. The formed new society acts under the different names: "post-industrial society", "information", "technetronic", "telecommunication" civilizations, etc. (D. Bell, R. Aron, O. Toffler, Z. Bzezhinsky, etc.). One of the priority values of the new civilization is the concept of "sustainable development". The article deals with the problem of sustainable development, is an important part of modern culture of peace. There is a growing body of literature, including in Kazakhstan that recognizes the importance of this concept. In these works, also in documents of UNESCO about the culture of the world, sustainable development is understood as the balanced condition of the globalized culture of the world, where the aspiration to preservation of ecological sustainability is combined with the actions directed to the eradication of poverty, social and ethnic cataclysms and conflicts. Relevance of this article lies in reasoning the revision of the values of the previous civilization and the introduction of a new culture of peace. The author considers the possibility of reaching a long-term state of "global balance" and "sustainable development" by mankind. Keywords: sustainable development, human capital, environmental culture, civilization, innovation, democracy.